Nível de informação do usuário sobre saúde bucal em Unidades de Atenção Básica - Cappellano, Maria Cecilia (2018)
In order to evaluate the level of information on oral health of the users of the Basic Health Units (BHU) and the Family Health Strategies (FHS), as a result of the health promotion and education actions of the dental team, a direct quiz with questions highlighting the most relevant aspects on the subject (office attendance, oral hygiene habits, dental caries, periodontal disease, oral health and its association with systemic diseases, pregnancy, smoking, use of dental prosthesis and oral cancer) for 400 adults who attend the units of each service, chosen by lot. Data collection obeyed the criteria of a sectional observational epidemiological study. BHU presented better values for oral hygiene habits, gum disease, bacterial plaque, mother-to-child bacterial transmission, caries transmissibility (translated into habits between mother and child in early childhood). Similar positive results include the application of the Oral Health Team guidelines, knowledge about caries, tartar, presence of bacteria in the circulation, smoking and its health damage, use of prosthesis and, in a negative way, ignorance about the self-examination of prevention of cancer. Responses to FHS were better in terms of office attendance, lectures and groups, and supervised and worse brushing in relation to transmissibility. The content of the answers shows that there are concepts such as caries transmissibility and periodontal diseases that need greater attention on the part of the professionals for their clarification. The aim of this study is to raise the awareness of dental health professionals of the primary care of their role in health education and its promotion, as transforming agents in their community of action.